Kiss Me Crafts / Raja Aisyah Zahira Raja Mohd Zamri ... [et al.] - Raja Mohd Zamri, Raja Aisyah Zahira; Saiful Azlan Shah, Anis Liyana; Sehat, Nur Farah Syazwani; Azmi, Nur Izni; Md Subahan, Annur Azlina; Ahmad Sharip, Siti Nursyaza (2015)
Kiss Me Crafts is a company that specializes in home decorative items that are cheap yet meets modern trend. We are located at A2, 9 Avenue, Taman Korporat, Putra Nilai, Persiaran Utama Bandar Baru Nilai 71800 Nilai, Negeri Sembilan and established on January 15th, 2016. Our company chose home decorative shops and retailers in Nilai. Nilai itself is well-known for the fabric materials that are sold in bulk and also for the wood furniture, but not for their home decorative items. We intend to sell our products to university student, who basically fill a quarter of Nilai and Sepang area, and new tenants who are living around the suburban area.